Oral rehabilitation in ceramic crown using digital flow: case report (Research, Society and Development, 2021)
Within clinical practice, digital dentistry is able to progressively dominate the adversities related to conventional molding techniques, as the mechanisms with IOS (intraoral scanner) provide more comfort to the patient, optimize work time and offer a forecast of the treatment. Thus, the selection of the type of ceramic will influence the conservation of the restoration. The aim of this study was to report a clinical case of rehabilitation of an upper molar with the contribution of digital flow, to obtain a metal-free total crown. Promptly after the clinical-radiographic opinion, a treatment was chosen for the patient, which consisted of exchanging a fractured crown made of injected lithium disilicate for a reamed one. The expulsive preparation was carried out with the 2067 drills to prepare the external straight angles and the internal ones with the 4138 to make them rounded. As for cementation, the best option for this case was the dual polymerization self-adhesive resin cement. Through the execution of this work, the patient's dental rehabilitation became feasible, capable of encouraging and assisting in future studies on fixed prostheses, performed in the digital workflow through the scanner, with simple handling and defined scanning.